A Course Design for Individualized Learning Leveraging Didactic Functions of Mobile Learning Devices - Schefer-Wenzl, Sigrid; Miladinovic, Igor (International Journal of Advanced Corporate Learning (iJAC), 2017)
Mobile computing and wireless technologies are transforming traditional educational patterns. The use of mobile devices for educational purposes led to what is known as mobile learning. In recent years, mobile learning strategies have been increasingly adopted in higher education. They support personalized, informal, situated, contextualized and ubiquitous learning. In practice, we have witnessed that courses in software engineering education often do not lead to the expected learning outcomes. In this paper, we will therefore present a motivating and learner-centered approach for mobile e-learning in application prototyping. We use mobile devices as key enabler serving different didactic functions in the context of learning, prototyping and collaboration.